The Role of Productive Zakat on the Empowerment of Street Vendors (Case Study of Baznas Medan - Ruhama, Intan; Sudiarti, Sri; Anggraini, Tuti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study is to analyze the role of productive zakat in increasing the empowerment of street vendors (PKL) micro-enterprises, to analyze how the performance of street vendors is, to analyze whether the productive zakat given by BAZNAS plays a role in the Empowerment of street vendors, and to analyze the results of empowering street vendors. This study used a descriptive qualitative method. This research was conducted on Medan Street vendors who received productive zakat from zakat institutions and on zakat institutions namely BAZNAS Medan. Technical Data analysis is carried out continuously, taking place during data collection and after data collection is complete. Ṫhe research results show that the distribution of zakat can be focused on human productivity so that the benefits will be felt consistently. This research is qualitative research with an in-depth analysis method so that productive zakat distributed by the BAZNAS Institute can be empowered the productivity of street vendors. The results of this study indicate that the main strength of the distribution of productive zakat by BAZNAS Medan is zakat as an obligation for able Muslims, while the main weakness is the difficulty of the facilitator in giving directions regarding the socialization of the marketing of goods and services produced by street vendors (mustahiq). The main opportunity is the strong community support for the implementation of productive zakat, while the main threat is the pressure on the cost of living experienced by mustahiq, which causes the misuse of the profits from the productivity of productive zakat funds into consumptive funds by mustahiq.